Uma proposta de aplicação de algoritmos criptográficos na comunicação via OPC em sistemas de automação industrial - Freitas Júnior, José Luiz de (2003)
Cryptographic techniques is usually applied to improved safety for transfemng information in Computer networks. This area is in constant evolution due to the growth of the world net -www. Facing on this context, a study is developed and presented in this work, based on theories, such as, the pattem OPC, the codes of linear blocks and the foundations of classic cryptography and public key, elucidating the main existent algorithms. A classic cryptographic System using codes of linear blocks is presented, with the puipose to obtaining safety in the communication through OPC in industrial automation Systems. An application, based on Client/Server model for safe exchange information between the client station and the server station is developed, using automation interfaces and a cryptographic algorithm (OPC server). A performance analysis of the developed OPC server is presented. Based on the studies developed in this work and on the result o f the performance analysis, the viability of using cryptographic techniques when transferring information through OPC is confirmed.